Insight on Ni(II) and Cu(II) complexes of biguanide derivatives developed as effective antimicrobial and antitumour agents. (29th January 2021) - Badea, Mihaela; Grecu, Maria Nicoleta; Chifiriuc, Mariana Carmen; Bleotu, Coralia; Popa, Marcela; Iorgulescu, Emilia Elena; Avram, Speranța; Uivarosi, Valentina; Munteanu, Alexandra‐Cristina; Ghica, Daniela; Olar, Rodica
Abstract : Six compounds of the types [M(dmbg)2 ]· n H2 O ((1 ) M: Ni, n = 0; (4 ) M: Cu, n = 1; Hdmbg: N, N ′‐dimethylbiguanide) and, respectively, [ML]· n H2 O (where (2 ) M: Ni, L: L 1, n = 0; (3 ) M: Ni, L: L 2, n = 0; (5 ) M: Cu, L: L1, n = 0 and (6 ) M: Cu, L: L2, n = 3, H2 L 1 : ligand resulted from the condensation of (1 ) with ammonia and formaldehyde and H2 L 2 : ligand resulted from the condensation of (4 ) with hydrazine and formaldehyde) were characterized as mononuclear species through information provided by NMR, electronic paramagnetic resonance (EPR) and UV–Vis spectroscopy as well as cyclic voltammetry. All data are consistent with macrocyclic formation by condensation. The complexes adopt a distorted square planar geometry resulting from the chelating behaviour of the corresponding ligands. The EPR spectra recorded after the addition of Cu(II) complexes into the corresponding Ni(II) complexes show a well resolved hyperfine structure with the superhyperfine pattern corresponding to four nitrogen atom donors. The cathodically shift of E pc2 for both series can be correlated with the increased stability of the M(I) species through macrocyclic ligands. Geometry optimization studies for complexes (2 ), (3 ), (5 ) and (6 ) have further confirmed the experimental data. The pharmacokinetic computational results indicate that the complexes exhibit medium to low intestinal absorption and slow blood–brain barrier permeability but low toxicity. Their predictive pharmacodynamic profiles show that the compounds present the ability to inhibit protease activity. By corroborating the results of the in silico analysis with the experimental ones, the most promising complexes for antimicrobial applications are (1 ) and (2 ) and, respectively, (4 ) and (6 ) for the development of novel antitumour strategies. Abstract : A series of Ni(II) and Cu(II) complexes with biguanide derivatives exhibit antimicrobial activity both on planktonic and biofilm‐embedded strains as well as cytotoxicity against HeLa and HCT8 tumour cells.